Using rapid antigen testing for early, safe return-to-work for healthcare personnel after SARS-CoV-2 infection in a healthcare system in Pakistan: A retrospective cross-sectional study - Unab Inayat Khan; Syed Faisal Mahmood; Sara Khan; Zahra Hasan; Ahmed Cheema; Asif Hakim; Shehreen Inayat Ali (Public Library of Science (PLoS), 2023)
Anticipating staff shortage during the Omicron variant surge, we modified the US Centers for Disease Control and Prevention's contingency guidelines at a healthcare system in Pakistan. Infected staff had a SARS-CoV-2 rapid antigen test after 5-7 days of isolation, to decide a safe return-to-work. This led to signifcant cost savings without compromising patient/staff safety.